Contact tracing following outbreak of Ebola virus disease in urban settings in Nigeria - Fawole, Olufunmilayo Ibitola (Pan Afr Med J, 2017)
An outbreak of Ebola virus disease occurred in Nigeria between July and September 2014. Contact tracing commenced in Lagos, and extended to Port Harcourt and Enugu as the outbreak continued to spread. A total of 899 contacts were traced. Contact tracing enhanced immediate identification of symptomatic contacts, some of whom eventually became cases. Contact tracing could be challenging in urban cities. However, use of electronic technology, adequate logistics, and highly skilled personnel enhanced the tracing of contacts to facilitate the successful containment of the outbreak. Nigeria was certified to be Ebola free on 21st October 2014. Ebola virus surveillance needs to be maintained to ensure the disease has been contained and to prevent future outbreaks. This case study aims to help trainees to review concepts, apply skills, and address challenges for contact tracing based on the experience of the Nigerian Field Epidemiology Training Network during the 2014 Ebola virus disease outbreak.